Analisis Kinerja Pemerintahan Desa Dalam Pengelolaan Alokasi Dana Desa Pada Desa Nirangkliung Kecamatan Nita Kabupaten Sikka - Marselina Yunelciante Bora; Henrikus Herdi; Yan Yanitza Salvanos (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to determine the performance of the Village Government in Managing Village Fund Allocations in Nirangkliung Village, Nita District, Sikka Regency. This research design is qualitative descriptive with data collection techniques in the form of observation, documentation and interviews. The type of data in this research is qualitative data with primary data sources and secondary data sources. Data analysis in this research takes the form of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the performance of the Village Government in Managing Village Fund Allocations is quite good, seen from several indicators, namely responsiveness, responsibility and accountability. However, there are two indicators that are not working well, namely productivity indicators and service quality. Therefore, the assessment of productivity and service quality in the Nirangkliung Village government must be improved. The preparation of activity programs must prioritize the programs contained in the Village Development Planning Conference as well as transparency from village government officials to the community in their accountability for managing Village Fund Allocations.